Editorial: Redefining and reconfiguring the idea of a university: Towards an African university of conscience, humanness and wonder - Hungwe, J. P.; Waghid, Y. (South African Journal of Higher Education, 2024)
Against the backdrop of an Africanisation imperative, universities in Africa seem to continuously redefine and reconfigure in search of social alignment, identity and relevance. It is for this reason that compelling processes, such as decolonisation, transformation and other higher education reform initiatives, are underscored by the primary imperative of pursuing social meaning and relevance. In post-colonial Africa, the imperative of Africanisation of the university has, though necessary, remained a contested topical discourse. This conceptual article seeks to contribute to the debate by drawing upon notions of conscience, humanness and wonder as possible anchors for the Africanisation of the university on the continent.